Chronicles of the royal family of Bonai (Odisha) - Pramanik, Rashmi, 1975-; Skoda, Uwe, 1973- (New Delhi : Manohar Publishers & Distributors, 2013)
On Bonai distirct, a princely state during the British Raj and its capital at Bonaigarh, located in the present-day Sundergarh district of Odisha.
Includes bibliographical references.
English and Oriya.
Keywords: Kings and rulers; India--Sundargarh (District); India--Odisha; Sundargarh (India : District) -- History; Sundargarh (India : District) -- Kings and rulers